Effect of Concentrated Growth Factor (CGF) on the Promotion of Osteogenesis in Bone Marrow Stromal Cells (BMSC) in vivo - Xia Chen (Nature Portfolio, 2018)
Abstract The therapeutic method traditionally used in bone defect reconstruction is autologous bone grafting. The most common problems affecting this type of repair approach are bone absorption and donor trauma. The approach taken in this study overcomes these problems. Bone marrow stromal cells (BMSCs) provided the crucial seed cells. Fibrin biological scaffolds were formed by combining the BMSCs with concentrated growth factor (CGF). BMSCs were isolated from Wistar rat femurs; CGF was prepared from rat heart blood. Five repair groups were created for comparative purposes: (A) CGF + BMSCs; (B) CGF; (C) collagen + BMSCs; (D) collagen; (E) blank. After three months, the rats were sacrificed, and histopathology and three-dimensional CT images produced. Bone regeneration was significantly higher in the (A) CGF + BMSC group; osteogenesis was lower in the (B) CGF and (C) collagen + BMSC groups, at very similar levels; the (D) collagen and (E) blank groups scored the lowest results. Our research suggests that combining CGF with BMSCs leads to the formation of fibrin scaffolds that have a powerful effect on osteogenesis as well as a subsidiary angiogenic effect. SEM images of the CGF scaffolds cultured with BMSCs confirmed good CGF biocompatibility. The superior osteoinductive activity of the CGF + BMSC combination makes it an excellent biomaterial for bone regeneration.